Surface softening in palladium nanoparticles: effects of a capping agent on vibrational properties. Issue 10 (27th February 2020) - Rebuffi, Luca; Mukherjee, Binayak; Siboni, Stefano; Young, Allison P.; Williams, Benjamin P.; Tsung, Chia-Kuang; Scardi, Paolo
Abstract : The presence of a capping agent (CTAB) on Pd nanoparticles produces a strong static disorder in the surface region. Abstract : The presence of a capping agent (CTAB) on Pd nanoparticles produces a strong static disorder in the surface region. This results in a surface softening, which contributes to an overall increase in the Debye–Waller coefficient measured by X-ray powder diffraction. Molecular dynamics and density functional theory simulations show that the adsorption-induced surface disorder is strong enough to overcome the effects of nanoparticle size and shape.